Tremor analysis with wearable sensors correlates with outcome after thalamic deep brain stimulation. (2020) - Rüegge, Dayle; Mahendran, Sujitha; Stieglitz, Lennart H.; Oertel, Markus F.; Gassert, Roger; Lambercy, Olivier; Baumann, Christian R.; Imbach, Lukas L.
Abstract: Introduction: Thalamic deep brain stimulation (DBS) provides excellent tremor control in most patients with essential tremor (ET). However, not all tremor patients show clinically significant improvement after DBS surgery. Currently, there is no reliable clinical or instrument-based measure to predict how patients respond to DBS. Therefore, we set out to provide a method for tremor outcome prediction prior to surgery. Methods: We retrospectively analysed quantitative tremor data collected with inertial measurement units (IMU) in 13 patients who underwent DBS surgery in the ventral intermediate nucleus of the thalamus (VIM). All patients were diagnosed with either ET or ET-plus according to current diagnostic criteria of the movement disorder society. We used linear and logistic regression models to evaluate the influence of different tremor characteristics on tremor outcome. Results: We found that the ratio between the amplitude of the first overtone and the amplitude of the fundamental frequency, denoted as the Harmonic Index, has a significant influence on tremor reduction after DBS surgery. This measure shows a strong correlation with the post-operative improvement of tremor outcome based on the Whiget Tremor Rating Scale. Conclusion: Based on these findings, we propose a novel approach to predict tremor outcome after DBS surgery. Quantitative tremor assessment adds to the preoperative prediction of DBS response and might therefore have a relevant clinical impact in the management of patients suffering from pharmacoresistant tremor. Highlights: Not all tremor patients show clinically significant improvement after thalamic deep brain stimulation. Quantitative tremor assessment based on wearable technology adds to the preoperative prediction of DBS response. Tremor analysis with wearable sensors might have a relevant clinical impact in the management of tremor patients